2018
DOI: 10.1590/0103-6440201801672
|View full text |Cite
|
Sign up to set email alerts
|

Implant Inclination and Horizontal Misfit in Metallic Bar Framework of Overdentures: Analysis By 3D-FEA Method

Abstract: The aim of this study was to evaluate by three-dimensional finite element analysis (3D-FEA) the biomechanics involved in bar-framework system for overdentures. The studied factors were latero-lateral angulation in the right implant (-10, -5, 0, 5 and 10 degrees), and different bar cross-sections (circular, Hader and oval) presenting horizontal misfits (50 or 150 µm) on the opposite implant. Positive angulation (5 and 10 degrees) for implant inclination to mesial position, negative angulation (-5 and -10 degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…26,27 However, few studies exist on the in vitro effect of posterior implant's inclination on the bone resorption and survival rates of the implant-supported fixed partial dentures, which makes our study results valuable. 16,17,[28][29][30] Our study exhibited that stress values for the crestal bone were the highest around the tilted posterior implants for both loading modes, which is in agreement with two previous studies. 16,17 Posterior implant inclination caused 34.25% higher bone stress for vertical loading, and 40.52% higher stress for oblique loading but this was the average of two peri-implant bone areas.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…26,27 However, few studies exist on the in vitro effect of posterior implant's inclination on the bone resorption and survival rates of the implant-supported fixed partial dentures, which makes our study results valuable. 16,17,[28][29][30] Our study exhibited that stress values for the crestal bone were the highest around the tilted posterior implants for both loading modes, which is in agreement with two previous studies. 16,17 Posterior implant inclination caused 34.25% higher bone stress for vertical loading, and 40.52% higher stress for oblique loading but this was the average of two peri-implant bone areas.…”
Section: Discussionsupporting
confidence: 93%
“…However, limited in vitro studies exist concerning the effects of the tilted implants on the biomechanics of the fixed partial dentures and the surrounding system. 16,17 There is also a lack of information about the comparison of stress levels at the peri-implant bone and the implant-abutment complex of posterior mandibular implants with different neck geometries, inclined angles, and diameters. Our hypothesis was that changing the neck platform design, inclination, and diameter of the posterior implant will cause different stress levels at the peri-implant bone area and implant-abutment complex.…”
Section: Introductionmentioning
confidence: 99%
“…Descriptives, advantages and limitations of the techniques are listed in Table 6. Within the 23 articles solely used modeling assessments, 10 investigated with SGA, 16,60‐69 1 with PSA, 70 1 with reverse torque test, 71 and 11 with FEA 10,72‐81 . All 11 studies established the FE model with 2 implants (five overdentures, seven 3‐unit frameworks), while no FEA study was found on complete arch prosthesis supported by multiple implants.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the FEA studies introduced levels of predetermined misfit into the FE models to calculate the resulting stresses concentrated in the implant system, including screws, framework, implants and peri‐implant bone (cortical and cancellous bone). The artificially induced misfit ranged from 5 ~ 300 μm on the vertical plane 73,75‐78,81 and 10 ~ 200 μm on the horizontal plane 10,72,74,79,80 . Besides, vertical bone loss (1.4 mm), 74 unilateral angular misfit (100 μm) 81 and axial/off‐axial forces (100 ~ 200 N) 75,81 were also simulated in different studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation